Le visage francophone de Chypre - Ioannou, Yiannis E. (Études helléniques / Hellenic Studies, 2007)
In spite of appearances, Francophony in Cyprus has played a role that is not only cultural but also indirectly political. The few articles published on the subject, examine the particular aspects of this presence. Based on this observation, this article attempts to assess the contribution of Francophony in Cyprus in relation to Cypriot cultural life. We recall very briefly passages from Rimbaud and their impact on the intellectual life, before presenting in detail certain French-speaking literary figures of the island. The francophone literature, sustained since Independence (1960) by a highly active French Cultural Centre, has opened for Cypriots a window on to a world other than the one forced upon them by their AngloSaxon oppressor for nearly a century (1878-1960). In addition, in the context of the postcolonial period from Independence to the present, French culture offers an alternative that cultivates and spreads the idea of a European identity and, more recently, of a united Europe as opposed to the British ascendancy. Moreover, it promotes a sensibility that counterbalances the model of mass consumption “imported especially during the last two decades.